The Call of the proper nouns in the Quran (Rhetorical Study) - Abdelrahman Moawad Ali Tahawi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
This research contains three objectives, the first of which is to extrapolate the positions of the call of the flags that are mentioned in the Qurâ€™anic verses and to form a clear picture of this type of call with the analysis of a number of Qurâ€™anic evidence rhetorically. The second is to follow what the rhetoricians dealt with regarding directing the discourse in the style of the appeal, and the use of the forms of the appeal in a way other than its original meaning. The third is to monitor the overall relationship between the question and the Qurâ€™anic call and the significance of this relationship. In writing this research, the researcher followed the inductive and analytical approaches by extrapolating and tracing the texts and then analyzing them rhetorically. The research concluded with several results, including: (1) The Noble Qur'an has numerous references to the call to science, therefore it is an honor for the herald in some cases and a mocking in others. (2) In many places, the Qur'anic verses adopted the method of calling, which is one of the methods of preparation and educational preparation that leads to attracting the caller's attention and urging him to approach and focus, as well as creating a sense of familiarity, grooming, and privacy that makes him feel how important it is, and the interest of the Qur'anic discourse in it makes him more ready to receive and comply.Â (3) The frequent occurrence of command, prohibition, and interrogation construction methods associated with the Qur'anic call, as well as their occurrence in the Holy text, is frequently accompanied by a semantic shift in which these methods separate their direct literal significance from other indications, which is known in the old rhetorical lesson as the idea of purposes. This change from literal to rhetorical meaning implies a unique capacity that aids in drawing the recipient's attention and maintaining his communication with the text at its most responsive and interactive level.Â ÙŠØØªÙˆÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¹Ù„Ù‰ Ø«Ù„Ø§Ø«Ø© Ø£Ù‡Ø¯Ø§ÙØŒ Ø£ÙˆÙ„Ù‡Ø§ Ø§Ø³ØªÙ‚Ø±Ø§Ø¡ Ù…ÙˆØ§Ø¶Ø¹ Ù†Ø¯Ø§Ø¡ Ø§Ù„Ø£Ø¹Ù„Ø§Ù… Ø§Ù„ØªÙŠ ÙˆØ±Ø¯Øª ÙÙŠ Ø§Ù„Ø³ÙˆØ± Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© ÙˆØªÙƒÙˆÙŠÙ† ØµÙˆØ±Ø© ÙˆØ§Ø¶ØØ© Ù„Ù‡Ø°Ø§ Ø§Ù„Ù†Ù…Ø·Â Ù…Ù† Ø£Ù†Ù…Ø§Ø· Ø§Ù„Ù†Ø¯Ø§Ø¡ Ù…Ø¹ ØªØÙ„ÙŠÙ„ Ø¹Ø¯Ø¯ Ù…Ù† Ø§Ù„Ø´ÙˆØ§Ù‡Ø¯ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© ØªØÙ„ÙŠÙ„Ø§ Ø¨Ù„Ø§ØºÙŠØ§. Ø«Ø§Ù†ÙŠÙ‡Ø§ ØªØªØ¨Ø¹ Ù…Ø§ ØªÙ†Ø§ÙˆÙ„Ù‡ Ø§Ù„Ø¨Ù„Ø§ØºÙŠÙˆÙ† Ø¨Ø´Ø£Ù† ØªÙˆØ¬ÙŠÙ‡ Ø§Ù„Ø®Ø·Ø§Ø¨ ÙÙŠ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ù†Ø¯Ø§Ø¡ØŒ ÙˆØ§Ø³ØªØ¹Ù…Ø§Ù„ ØµÙŠØº Ø§Ù„Ù†Ø¯Ø§Ø¡ ÙÙŠ ØºÙŠØ± Ù…Ø¹Ù†Ø§Ù‡ Ø§Ù„Ø£ØµÙ„ÙŠ. Ø«Ø§Ù„Ø«Ù‡Ø§ Ø±ØµØ¯ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø¨ÙŠÙ† Ø§Ù„Ø§Ø³ØªÙÙ‡Ø§Ù… ÙˆØ§Ù„Ù†Ø¯Ø§Ø¡ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ ÙˆÙ…Ø¹Ø²Ù‰ Ù‡Ø°Ù‡ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø©. ÙˆØ§ØªØ¨Ø¹ Ø§Ù„Ø¨Ø§ØØ« ÙÙŠ ÙƒØªØ§Ø¨Ø© Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ù†Ù‡Ø¬ÙŠÙ† Ø§Ù„Ø§Ø³ØªÙ‚Ø±Ø§Ø¦ÙŠ ÙˆØ§Ù„ØªØÙ„ÙŠÙ„ÙŠ ÙˆØ°Ù„Ùƒ Ø¨Ø§Ø³ØªÙ‚Ø±Ø§Ø¡ ÙˆØªØªØ¨Ø¹ Ø§Ù„Ù†ØµÙˆØµ Ø«Ù… ØªØÙ„ÙŠÙ„Ù‡Ø§ Ø¨Ù„Ø§ØºÙŠØ§. ÙˆÙ‚Ø¯ Ø®Ù„Øµ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø¹Ø¯Ø© Ù†ØªØ§Ø¦Ø¬ Ù…Ù†Ù‡Ø§: (1) ØªØªØ¹Ø¯Ø¯ Ø¯Ù„Ø§Ù„Ø§Øª Ø§Ù„Ù†Ø¯Ø§Ø¡ Ø¨Ø§Ù„Ø¹Ù„Ù…ÙŠØ© ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… ÙØªÙƒÙˆÙ† ÙÙŠ Ø¨Ø¹Ø¶ Ø§Ù„Ø´ÙˆØ§Ù‡Ø¯ ØªØ´Ø±ÙŠÙØ§ Ù„Ù„Ù…Ù†Ø§Ø¯Ù‰ ÙˆØªÙƒÙˆÙ† Ø³Ø®Ø±ÙŠØ© Ù…Ù†Ù‡ ÙÙŠ Ø¨Ø¹Ø¶Ù‡Ø§ Ø§Ù„Ø¢Ø®Ø±.(2) Ø§Ø¹ØªÙ…Ø¯Øª Ø§Ù„Ø³ÙˆØ± Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ù†Ø¯Ø§Ø¡ ÙÙŠ Ù…ÙˆØ§Ø¶Ø¹ ÙƒØ«ÙŠØ±Ø© ÙˆÙ‡Ùˆ Ø£ØØ¯ Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„ØªÙˆØ·Ø¦Ø© ÙˆØ§Ù„ØªÙ‡ÙŠØ¦Ø© Ø§Ù„ØªØ±Ø¨ÙˆÙŠØ© Ø§Ù„ØªÙŠ ØªØ¤Ø¯ÙŠ Ø¥Ù„Ù‰ Ø¬Ø°Ø¨ Ø§Ù†ØªØ¨Ø§Ù‡ Ø§Ù„Ù…Ù†Ø§Ø¯ÙŠ ÙˆØØ«Ù‡ Ø¹Ù„Ù‰ Ø§Ù„Ø§Ù‚ØªØ±Ø§Ø¨ ÙˆØ§Ù„ØªØ±ÙƒÙŠØ² ÙˆØ¥ÙŠØ¬Ø§Ø¯ Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„Ø£Ù„ÙØ© ÙˆØ§Ù„Ø§Ø³ØªÙ…Ø§Ù„Ø© ÙˆØ§Ù„Ø®ØµÙˆØµÙŠØ© Ø§Ù„ØªÙŠ ØªØ´Ø¹Ø±Ù‡ Ø¨Ù…Ø¯Ù‰ Ø£Ù‡Ù…ÙŠØªÙ‡ ÙˆØ§Ù‡ØªÙ…Ø§Ù… Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ Ø¨Ù‡Â ÙŠØ¬Ø¹Ù„Ù‡ Ø£ÙƒØ«Ø± Ø§Ø³ØªØ¹Ø¯Ø§Ø¯Ø§ Ù„Ù„ØªÙ„Ù‚ÙŠ ÙˆØ§Ù„Ø§Ù…ØªØ«Ø§Ù„. (3) ÙƒØ«Ø±Ø© ÙˆØ±ÙˆØ¯ Ø§Ù„Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„Ø¥Ù†Ø´Ø§Ø¦ÙŠØ© Ù…Ù† Ø£Ù…Ø± ÙˆÙ†Ù‡ÙŠ ÙˆØ§Ø³ØªÙÙ‡Ø§Ù… Ù…Ù‚ØªØ±Ù†Ø© Ù…Ø¹ Ø§Ù„Ù†Ø¯Ø§Ø¡ Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠ ÙˆÙƒØ«ÙŠØ±Ø§Ù‹ Ù…Ø§ ÙŠÙƒÙˆÙ† ÙˆØ±ÙˆØ¯Ù‡Ø§ ÙÙŠ Ø§Ù„Ù†Øµ Ø§Ù„ÙƒØ±ÙŠÙ… Ù…ØµØÙˆØ¨Ø§ Ø¨ØªØÙˆÙ„ Ø¯Ù„Ø§Ù„ÙŠ ØªÙØ§Ø±Ù‚ ÙÙŠÙ‡ Ù‡Ø°Ù‡ Ø§Ù„Ø£Ø³Ø§Ù„ÙŠØ¨ Ø¯Ù„Ø§Ù„ØªÙ‡Ø§ Ø§Ù„ØØ±ÙÙŠØ© Ø§Ù„Ù…Ø¨Ø§Ø´Ø±Ø© Ø¥Ù„Ù‰ Ø¯Ù„Ø§Ù„Ø§Øª Ø£ÙØ®Ø± ÙˆÙ‡Ùˆ Ù…Ø§ ÙŠØ¹Ø±Ù ÙÙŠ Ø§Ù„Ø¯Ø±Ø³ Ø§Ù„Ø¨Ù„Ø§ØºÙŠ Ø§Ù„Ù‚Ø¯ÙŠÙ… Ø¨ÙÙƒØ±Ø© Ø§Ù„Ø£ØºØ±Ø§Ø¶. ÙˆÙ‡Ø°Ø§ Ø§Ù„ØªØÙˆÙ„ Ù…Ù† Ø§Ù„Ø¯Ù„Ø§Ù„Ø© Ø§Ù„ØØ±ÙÙŠØ© Ø§Ù„Ù…Ø¨Ø§Ø´Ø±Ø© Ø¥Ù„Ù‰ Ø§Ù„Ø¯Ù„Ø§Ù„Ø© Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© ÙŠÙ†Ø·ÙˆÙŠ Ø¹Ù„Ù‰ Ù‚Ø¯Ø±Ø© Ù„Ø§ÙØªØ© ØªØ³Ù‡Ù… ÙÙŠ Ø¬Ø°Ø¨ Ø§Ù†ØªØ¨Ø§Ù‡ Ø§Ù„Ù…ØªÙ„Ù‚ÙŠ ÙˆØ¨Ù‚Ø§Ø¡ ØªÙˆØ§ØµÙ„Ù‡ Ù…Ø¹ Ø§Ù„Ù†Øµ ÙÙŠ Ø£ÙƒØ«Ø± ØØ§Ù„Ø§ØªÙ‡ ØªØ¬Ø§ÙˆØ¨Ø§ ÙˆØªÙØ§Ø¹Ù„Ø§.